2023
DOI: 10.1096/fj.202201793rr
|View full text |Cite
|
Sign up to set email alerts
|

FTOrepressesNLRP3‐mediated pyroptosis and alleviates myocardial ischemia–reperfusion injury via inhibitingCBL‐mediated ubiquitination and degradation of β‐catenin

Abstract: Cardiac ischemia/reperfusion (I/R) injury is a complicated pathological event, which has close association with pyroptosis. This study uncovered the regulatory mechanisms of fat mass and obesity-associated protein (FTO) in NLRP3-mediated pyroptosis during cardiac I/R injury. H9c2 cells were stimulated with oxygenglucose deprivation/reoxygenation (OGD/R). Cell viability and pyroptosis were detected by CCK-8 and flow cytometry. Western blotting or RT-qPCR was performed to analyze target molecule expression. NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(69 reference statements)
4
2
0
Order By: Relevance
“…Earlier research discovered that FTO inhibits OS in cerebral I/R injury by mediating m6A modification of Nrf2 mRNA 30 . As a demethylase, FTO is noted to suppress m6A modification of proteins to afflict their stability 43,44 . Our data proved that FYN was upregulated after tMCAO/R treatment and FTO overexpression reduced FYN expression by decreasing FYN mRNA m6A modification.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Earlier research discovered that FTO inhibits OS in cerebral I/R injury by mediating m6A modification of Nrf2 mRNA 30 . As a demethylase, FTO is noted to suppress m6A modification of proteins to afflict their stability 43,44 . Our data proved that FYN was upregulated after tMCAO/R treatment and FTO overexpression reduced FYN expression by decreasing FYN mRNA m6A modification.…”
Section: Discussionsupporting
confidence: 65%
“… 30 As a demethylase, FTO is noted to suppress m6A modification of proteins to afflict their stability. 43 , 44 Our data proved that FYN was upregulated after tMCAO/R treatment and FTO overexpression reduced FYN expression by decreasing FYN mRNA m6A modification. Considering that FYN may regulate the process of cerebral I/R, 14 we also designed related experiments to ascertain the specific effects of FYN on cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The pyroptosis‐related genes play essential roles in the occurrence and development of cardiovascular disease and affect the process and outcomes. Inhibiting myocardial pyroptosis could improve cardiac remodelling 44 . This study confirmed 13 optimal pyroptosis genes to be downregulated or upregulated in ICM, demonstrating a necessary diagnostic and regulating potential.…”
Section: Discussionsupporting
confidence: 57%
“…Inhibiting myocardial pyroptosis could improve cardiac remodelling. 44 This study confirmed 13 optimal pyroptosis genes to be downregulated or upregulated in ICM, demonstrating a necessary diagnostic and regulating potential. We identified these genes as highly accurate biomarkers for the effective diagnosis of ICM enabling early treatment and intervention.…”
Section: Discussionsupporting
confidence: 57%